Direct Current Arc Plasma Synthesis of Superdisperced Powder Materials in "Tungsten-Carbon" System; Surface Modification of Materials by Ion Beams (SMMIB-2019) - Pak A. Ya. Aleksandr Yakovlevich (Ion-Assisted Coating Deposition. Poster Session, 2019)
Заглавие с экрана